Strategi Guru BK dalam Mengembangkan Kesiapan Karir Peserta Didik Menghadapi tantangan Society 5.0 - Wahyu Almizri; Yusuf Akhmad (Empowerment Counseling Journal, 2025)
The Society 5.0 era brings significant changes to various aspects of life, including education, with demands for the younger generation to be career-ready and adaptive, innovative, and competitive. The main challenges faced by students include low digital literacy, weak non-technical skills, and the gap between education and the needs of the workplace. This study aims to analyze the strategies of Guidance and Counseling (BK) teachers in developing students' career readiness to face the challenges of Society 5.0. The research method used a Systematic Literature Review (SLR) approach by examining various scientific articles, academic books, and relevant research reports published between 2015 and 2023. The results of the study indicate that effective strategies of BK teachers include the use of digital technology in counseling services, strengthening soft skills, collaboration with parents and industry, and integrating career-based implementations. Obstacles found include limited facilities, teacher workload, and low digital-based counseling training. Therefore, increasing the professional capacity of BK teachers and supporting educational policies is essential. This study concludes that BK teachers play a role as agents of change in preparing students to be ready to face the challenges and take advantage of the opportunities of the Society 5.0 era.